Comparative Pharmacokinetics/Pharmacodynamic Modeling on Three Brands of 10% Enrofloxacin Oral Formulations in Broiler Chickens - Gberindyer, Fidelis Aondover; Wannang, Noel; Akwuobu, Chinedu Adive (International Journal of Poultry Science, 2010)
A comparative plasma pharmacokinetics/Pharmacodynamic modeling of enrofloxacin following administration of three brands of 10% enrofloxacin was studied in healthy broiler chickens using a randomized and parallel design. Pre-treatment and post-treatment samples were obtained from brachial or right jugular veins after having administered 20 mg/kg b.w of enrofloxacin at 0, 0.5, 1, 2, 3, 4, 6, 8, 10, 12 and 24 h. Plasma samples were analyzed for enrofloxacin concentration by a simple agar disk diffusion microbiological assay. Selected pharmacokinetics parameters were calculated using a non-compartmental model. There was a significant difference in the plasma concentration-time and pharmacokinetics profiles (p